(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2021)
The use of synthetic surgical mesh has become the standard of the hernia repair, but so far the implementation of mesh does not seem to have reduced the risk of recurrence while it is believed that it would only delay it. Objective: determine the efficiency to long term (5 years) of the hernioplasty with polypropylene mesh in patients with incisional hernia intervened in the "Abel Gilbert Pontón" Hospital. Methodology: is carried out a study quantitative, observational longitudinal, retrospective, not experimental in which is included consecutive patients with incisional hernia in who was made hernioplasty with polypropylene mesh: 45 cases without recurrence and 34 with recurrence, treated in Abel Gilbert hospital from Guayaquil - Ecuador, between 2005 and 2015. The analysis statistical is carried out with tables actuarial and of mortality. Results: the first year, the rate of no recurrence is of the 100%, to the third year is of 98% and the fifth year is of the 65%. The cumulative 5-year rate is 40% at 5 years. The complications are produced with greater frequency in patients that recurred (23,5% vs. 2,2%; P 0,06). The presence of factors of risk are associated significantly with the presence of recurrence (70,6% vs. 37,8%;) (P 0,021) Conclusions: the rate of no recurrence at 5 years in patients with incisional hernia and hernioplasty with polypropylene mesh, is low.